Questionnaire Development and Identification of Factors Contributing to Non-Prescription Antibiotic Selling Behavior in Surabaya Community Setting - Dewi Paskalia Andi Djawaria; Adji Prayitno Setiadi; Eko Setiawan (Faculty of Pharmacy, Universitas Gadjah Mada)
The selling practice of antibiotics without prescription is one of serious problems in the global health sector, especially in the developing countries. Nevertheless, the significant driver of such pratices had never been identified yet. The aim of this study was to identify the contributing factors of the selling practice of antibiotics without prescription in the drug stores (apotek). The identification was conducted using a new developed questionnaire. The contributing factors of such practices, found in the literature, were used to develop the questionnaire. The face and content validity were conducted using expert opinion, while the construct validity was conducted using the Spearman correlation test. The reliability of the questionnaire was identified using Cronbach’s Alpha test. The dominant factors of the selling practice of antibiotics without prescription was identified by using descriptive analysis and the factor analysis methods. The final questionnaire consisted of 40 questions and the value of the Cronbach’s Alpha and the calculated R were 0.955 and 0.368-0.867, consecutively. There were 91 workers of apotek in Surabaya who were involved in the contributing factors identification process. Findings of the factor analysis emphasized that the most dominant factor was the attitude of workers that allowed the selling practice of antibiotics without prescription (28.3%). The financial issue was found as the second most dominant factors causing the selling practice of antibiotics without prescription (8.66%). Owing to these identified factors, there is a need to make a regulation with a strict punishment in order to prevent the habit of selling and purchasing the antibiotics without prescription in the apotek in Surabaya.